Family law and social policy - "Eekelaar, John" (London, 1984)
The first edition Family Law and Social Policy received critical acclaim. The Law Quarterly Review 'Modern legal scholarship at its best...' In this second edition John Eekelaar has retained an overall structure based on the three primary functions of current law and practice: the protection of individuals within the family, the provision of an adjustment mechanism when families break down, and the support of family living. However, the book has been developed to provide a coherent re-thinking of the basic principles upon which family law operates. The author argues that the central problems of family law today spring from the role of the family as the universal agency for the provision of child care, and that consequently the solutions to those problems can only be found by focusing attention on children and the child-care function. This approach allows a fresh appraisal to be made of some of the traditional concerns of family law, and raises serious questions about the nature and role of children's rights.
Keywords: Family law .